Controlling cavitation‐based image contrast in focused ultrasound histotripsy surgery. Issue 1 (27th January 2014) - Allen, Steven P.; Hall, Timothy L.; Cain, Charles A.; Hernandez‐Garcia, Luis
<x xml:space="preserve">Abstract</x> Purpose To develop MRI feedback for cavitation‐based, focused ultrasound, tissue erosion surgery (histotripsy), we investigate image contrast generated by transient cavitation events. Methods Changes in GRE image intensity are observed while balanced pairs of field gradients are varied in the presence of an acoustically driven cavitation event. The amplitude of the acoustic pulse and the timing between a cavitation event and the start of these gradient waveforms are also varied. The magnitudes and phases of the cavitation site are compared with those of control images. An echo‐planar sequence is used to evaluate histotripsy lesions in ex vivo tissue. Results Cavitation events in water cause localized attenuation when acoustic pulses exceed a pressure threshold. Attenuation increases with increasing gradient amplitude and gradient lobe separation times and is isotropic with gradient direction. This attenuation also depends upon the relative timing between the cavitation event and the start of the balanced gradients. These factors can be used to control the appearance of attenuation while imaging ex vivo tissue. Conclusion By controlling the timing between cavitation events and the imaging gradients, MR images can be made alternately sensitive or insensitive to cavitation. During therapy, these images can be used to isolate contrast generated by cavitation. Magn Reson Med 73:204–213, 2015. © 2014 Wiley Periodicals, Inc.